Assessing syntactic deficits in Chinese Broca's aphasia using the Northwestern Assessment of Verbs and Sentences-Chinese (NAVS-C). Issue 7 (2nd July 2016) - Wang, Honglei; Thompson, Cynthia K.
Abstract : Background : English-speaking patients with Broca's aphasia and agrammatism evince difficulty with complex grammatical structures, including verbs and sentences. A few studies have found similar patterns among Chinese-speaking patients with Broca's aphasia, despite structural differences between these two languages. However, no studies have explicitly examined verb properties, including the number and optionality of arguments (participant roles) selected by the verb, and only a few studies have examined sentence deficits among Chinese patients. In addition, there are no test batteries presently available to assess syntactically important properties of verbs and sentences in Chinese patients. Aims : This study used a Chinese version of the Northwestern Assessment of Verbs and Sentences (NAVS), originally developed for English speakers with aphasia, to examine the verb and sentence deficit patterns among Chinese speakers with aphasia. As in the original NAVS, the Chinese version (NAVS-C) assessed verbs by the number and optionality of arguments as well as sentence canonicity, in the both production and comprehension. Methods and Procedures : Fifteen Chinese patients with Broca's aphasia and 15 age-matched healthy normal controls participated in this study. All NAVS-C tests were administered, in which participants were asked either to produce or to identify verbs and sentences coinciding with action pictures. Outcomes & R esults : Despite grammatical differences between Chinese and English, the impairment caused by the structural complexity of verbs and sentences was replicated in Chinese-speaking patients using the NAVS-C. Verbs with more arguments were significantly more impaired than those with fewer arguments and verbs with optional arguments were significantly more impaired than those with obligatory arguments. One deviation from English-speaking patients, however, is that the Chinese-speaking patients exhibited greater difficulty with subject relative clauses than with object relative clauses because the former, rather than the latter, involve noncanonical order in Chinese. Similar to English-speaking patients, Chinese patients exhibited more difficulty with object-extracted wh-questions than with subject-extracted wh-questions, suggesting that wh-movement in Logical Form may also cause processing difficulty. Moreover, Chinese-speaking patients exhibited similar performance in both production and comprehension, indicating the deficits in both modalities. Conclusions : The number and optionality of verb arguments as well as the canonicity of the Agent–Theme order in sentences impact Chinese-speaking individuals with aphasia as they do in the case of English-speaking patients. These findings indicate that the NAVS-C is a useful tool for detailing deficit patterns associated with syntactic processing in patients with aphasia cross-linguistically.